Alcohol‐induced IL‐1β in the brain is mediated by NLRP3/ASC inflammasome activation that amplifies neuroinflammation. Issue 1 (26th April 2013) - Lippai, Dora; Bala, Shashi; Petrasek, Jan; Csak, Timea; Levin, Ivan; Kurt‐Jones, Evelyn A.; Szabo, Gyongyi
Abstract : Chronic alcohol‐induced neuroinflammation is mediated by the NLRP3 inflammasome, is augmented by TLR4, and involves HMGB1. Abstract : Alcohol‐induced neuroinflammation is mediated by proinflammatory cytokines, including IL‐1β. IL‐1β production requires caspase‐1 activation by inflammasomes—multiprotein complexes that are assembled in response to danger signals. We hypothesized that alcohol‐induced inflammasome activation contributes to increased IL‐1β in the brain. WT and TLR4‐, NLRP3‐, and ASC‐deficient (KO) mice received an ethanol‐containing or isocaloric control diet for 5 weeks, and some received the rIL‐1ra, anakinra, or saline treatment. Inflammasome activation, proinflammatory cytokines, endotoxin, and HMGB1 were measured in the cerebellum. Expression of inflammasome components (NLRP1, NLRP3, ASC) and proinflammatory cytokines (TNF‐α, MCP‐1) was increased in brains of alcohol‐fed compared with control mice. Increased caspase‐1 activity and IL‐1β protein in ethanol‐fed mice indicated inflammasome activation. TLR4 deficiency protected from TNF‐α, MCP‐1, and attenuated alcohol‐induced IL‐1β increases. The TLR4 ligand, LPS, was not increased in the cerebellum. However, we found up‐regulation of acetylated and phosphorylated HMGB1 and increased expression of the HMGB1 receptors (TLR2, TLR4, TLR9, RAGE) in alcohol‐fed mice. NLRP3‐ or ASC‐deficient mice were protected from caspase‐1 activation and alcohol‐induced IL‐1β increase in the brain. Furthermore, in vivo treatment with rIL‐1ra prevented alcohol‐induced inflammasome activation and IL‐1β, TNF‐α, and acetylated HMGB1 increases in the cerebellum. Conversely, intracranial IL‐1β administration induced TNF‐α and MCP‐1 in the cerebellum. In conclusion, alcohol up‐regulates and activates the NLRP3/ASC inflammasome, leading to caspase‐1 activation and IL‐1β increase in the cerebellum. IL‐1β amplifies neuroinflammation, and disruption of IL‐1/IL‐1R signaling prevents alcohol‐induced inflammasome activation and neuroinflammation. Increased levels of acetylated and phosphorylated HMGB1 may contribute to alcoholic neuroinflammation.